2012
DOI: 10.1371/journal.pone.0046092
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy Contributes to Ischemic Postconditioning-Induced Neuroprotection against Focal Cerebral Ischemia in Rats

Abstract: BackgroundIschemic postconditioning (IPOC), or relief of ischemia in a stuttered manner, has emerged as an innovative treatment strategy to reduce programmed cell death, attenuate ischemic injuries, and improve neurological outcomes. However, the mechanisms involved have not been completely elucidated. Recent studies indicate that autophagy is a type of programmed cell death that plays elusive roles in controlling neuronal damage and metabolic homeostasis. This study aims to determine the role of autophagy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 44 publications
3
88
1
Order By: Relevance
“…39 Using a rat stroke mode, a significant decrease of p62, indication of autophagy activation, was not observed until 6 h reperfusion. 30 In contrast, in our ATF6-KI mice, we showed that activation of the ATF6 UPR branch significantly reduces the protein levels of p62 in the post-ischemic brain at 1 h reperfusion, suggesting earlier onset of increased autophagic activity ( Figure 5(c)). This activation of autophagy was likely mediated through decreased levels of phosphorylated mTOR, a key inhibitory regulator of autophagy.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…39 Using a rat stroke mode, a significant decrease of p62, indication of autophagy activation, was not observed until 6 h reperfusion. 30 In contrast, in our ATF6-KI mice, we showed that activation of the ATF6 UPR branch significantly reduces the protein levels of p62 in the post-ischemic brain at 1 h reperfusion, suggesting earlier onset of increased autophagic activity ( Figure 5(c)). This activation of autophagy was likely mediated through decreased levels of phosphorylated mTOR, a key inhibitory regulator of autophagy.…”
Section: Discussioncontrasting
confidence: 62%
“…In agreement with a previous report, we found a significant decrease of p62 in the ipsilateral cortex of both wild-type and ATF6-KI mice ( Figure 5(c)). 30 Levels of p-mTOR continued to be significantly lower in ATF6-KI mice after stroke ( Figure 5(c)). Although a similar trend of decreased p-mTOR levels after stroke appeared in wild-type mice, differences did not reach statistical significance at both reperfusion times.…”
Section: 28mentioning
confidence: 88%
“…To date, the neuroprotective mechanism underlying IPostC has been investigated widely and has been found to be related to the suppression of oxidative stress, 18 endoplasmic stress, 19 cell apoptosis and autophagy, 20 and the inflammatory response. 21 Among them, oxidative stress is a major cause of necrotic and apoptotic cell death after I/R, 22 and IPostC was reported to reduce protein oxidization by increasing the levels of antioxidants including SOD and catalase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that autophagy is involved in the neural death pathway that follows cerebral ischemia, and scientists have already monitored autophagic processes in vivo in live stroke patients (Tian et al 2010). The role of autophagy in ischemic stroke is still debated: it has both protective and detrimental effects (Sheng et al 2010;Yan et al 2011;Gao et al 2012). It has been reported that Ginsenoside Rb1, one of major compounds in SMI, could alleviate ischemia/reperfusion insults in rats and that an autophagic mechanism was involved in the benefits ); these findings indicated that SMI might have a similar mechanism against ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%